Many of the kids are not alright: Material hardship among children in the United States. (May 2020) - Rodems, Richard; Shaefer, H. Luke
Highlights: Children reside in households with hardship rates two to four times higher than seniors. The majority of children in households with hardship are above the poverty line, a third are above 200% of the poverty line. There are strong racial disparities in the risk of hardship. Abstract: The material well-being of children has profound implications for a variety of social and health outcomes. This paper provides estimates of the prevalence and intensity of material hardship among children by various demographic groups and reveals stark disparities by race and educational attainment. According to a pooled sample of the nationally-representative Survey of Income and Program Participation (SIPP) 36.5% of children lived in households reporting at least one form of material hardship, such as food insecurity, inability to pay essential household bills, inability to access medical care due to cost, or substandard and overcrowded housing. This is well above the proportion considered to be below the income poverty line (18.4%). Children were more likely to live in households experiencing material hardship than seniors.